Association Between Pre-Hospital e-Education via QR Code and Hospital Stay in Inguinal Hernia Patients Undergoing General Anaesthesia: A Retrospective Study - Ma G; Jiang P; Miao C; Huang Y; Li H; Zhao Y (Journal of Multidisciplinary Healthcare)
Guozhen Ma,1 Pengjun Jiang,2 Chuyuan Miao,1 Yanhui Huang,1 Huiping Li,1 Yongling Zhao3 1Day Surgery Care Unit, Shenzhen Nanshan People’s Hospital, Shenzhen, Guangdong, People’s Republic of China; 2Department of Anorectal Surgery, Shenzhen Nanshan People’s Hospital, Shenzhen, Guangdong, People’s Republic of China; 3Department of Gastrointestinal Surgery, Shenzhen Nanshan People’s Hospital, Shenzhen, Guangdong, People’s Republic of ChinaCorrespondence: Pengjun Jiang, Department of Anorectal Surgery, Shenzhen Nanshan People’s Hospital, Shenzhen, Guangdong, People’s Republic of China, Email 2020T0775@pwu.edu.phPurpose: Exploring the retrospective analysis of the association between pre-hospital e-education via QR code and the hospital stay for inguinal hernia patients undergoing general anesthesia.Patients and Methods: A retrospective study was conducted to explore the association between pre-hospital e-education utilizing QR code and hospital stay in patients with inguinal hernia repair under general anesthesia between August 2022 to June 2024. Patients were categorized into two groups based on their engagement with the pre-hospital e-education: those who accessed the pre-hospital e-education (viewing group) and those who did not (non-viewing group). The t-tests or Mann–Whitney U-tests were utilized to compare the means of the two groups, while the chi-square test was used to assess the rates between the two groups. To further explore the relationship between pre-hospital e-education and hospital stay, as well as other related factors, correlation analysis and multiple linear regression analysis were carried out.Results: There were significant differences in the patient’s hospital stay, the time to first postoperative ambulation and dietary, anxiety, pain, and patient satisfaction. The analyses revealed statistically significant correlations between viewing pre-hospital e-education via QR code and hospital stay, the time to first postoperative ambulation and dietary, anxiety, pain, as well as patients’ satisfaction (P< 0.05). This fully adjusted linear regression analysis revealed a significant negative correlation between viewing the pre-hospital e-education and hospital stay (β = − 4.06, 95% CI: − 6.43, − 1.70; P =0.002). Similarly, a negative correlation was observed between viewing the pre-hospital e-education and the time to first ambulation (β = − 0.71, 95% CI: − 1.25, − 0.17; P =0.015), as well as the time to first postoperative dietary (β = − 1.20, 95% CI: − 1.71, − 0.34; P =0.006) after controlling for relevant covariates.Conclusion: Effective pre-hospital e-education via online QR codes may reduce hospital stay and improve the patient experience in day surgery under general anesthesia.Keywords: pre-hospital, e-education, inguinal hernia, general anesthesia, day surgery, hospital stay